The design and synthesis of redox-responsive oridonin polymeric prodrug micelle formulation for effective gastric cancer therapy. Issue 13 (22nd March 2021) - Xu, Luzhou; Zhu, Lei; Zheng, Kai; Liu, Junlou; Tian, Panpan; Hu, Di; Wang, Qianqian; Zuo, Qiaoyun; Ouyang, Xiaosong; Dai, Yanna; Fu, Yuxian; Dai, Xinyi; et al.
Abstract : Novel redox-responsive oridonin polymeric prodrug micelles were prepared and it can effectively inhibit gastric cancer. Abstract : Advanced gastric cancer (GC) is a significant threat to human health. Oridonin (ORI), isolated from the Chinese herb Rabdosia rubescens, has demonstrated great potential in GC therapy. However, the application of ORI in the clinic was greatly hindered by its poor solubility, low bioavailability, and rapid plasma clearance. Herein, a simple and novel redox-sensitive ORI polymeric prodrug formulation was synthesized by covalently attaching ORI to poly(ethylene glycol)- block -poly(l -lysine) via a disulfide linker, which can self-assemble into micelles (P-ss-ORI) in aqueous solutions and produce low critical micelle concentrations (about 10 mg L −1 ), characterized by small size (about 80 nm), negative surface charge (about −12 mV), and high drug loading efficiency (18.7%). The in vitro drug release study showed that P-ss-ORI can rapidly and completely release ORI in a glutathione (GSH)-rich environment and under low pH conditions. Moreover, in vitro and in vivo investigations confirmed that P-ss-ORI could remarkably extend the blood circulation time of ORI, enrich in tumor tissue, be effectively endocytosed by GC cancer cells, and quickly and completely release the drug under high intracellular GSH concentrations and low pH conditions, all these characteristics ultimately inhibit the growth of GC. This redox and pH dual-responsive P-ss-ORI formulation provides a useful strategy for GC treatment.